2022
DOI: 10.1136/bmjgh-2022-010313
|View full text |Cite
|
Sign up to set email alerts
|

Development and implementation of the maternal and child health Handbook in Angola

Abstract: Although the maternal and child health (MCH) Handbook is widely used in many countries, its development and implementation process has not been sufficiently documented in scientific publications. This is a report of how the Angola MCH Handbook was developed, what challenges we encountered during its implementation and how they were solved. Leading the process was the MCH Handbook Committee set up to develop the MCH Handbook and implement the programme in liaison with various stakeholders. We developed the MCH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Preliminary findings from its pilot use prior to intervention launch [ 13 ] showed the MCH handbook was well received (unpublished results), and mothers may have actively sought to attend antenatal care to get the handbook. Consequently, the MCH handbook intervention may have worked as an incentive to modify demand-side factors in initiating antenatal care use consistent with the trial hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary findings from its pilot use prior to intervention launch [ 13 ] showed the MCH handbook was well received (unpublished results), and mothers may have actively sought to attend antenatal care to get the handbook. Consequently, the MCH handbook intervention may have worked as an incentive to modify demand-side factors in initiating antenatal care use consistent with the trial hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we administered our intervention package after the MCH handbook was designed through the MCH handbook committee comprising members from the Ministry of Health in Angola, the WHO, UNICEF, JICA, and local bodies (including the Angolan Pediatric Society). The MCH handbook development process in Angola has been previously reported [ 12 , 13 ]. The study design identified in the formative phase involved a community-wide distribution of the MCH handbook with its supplementary interventions.…”
Section: Methodsmentioning
confidence: 99%
“…17 Several interventions have been implemented to improve continuity, for example, MCH booklets introduced in Angola. 18 Previous reviews on MCH in high-income countries have also emphasised the importance of strengthening continuity, highlighting this as a priority area for research in LMICs. 19 Participatory approaches by engaging with the people who will ultimately interact with the intervention have drawn interest in recent years.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…Continuity can have a positive effect on maternal and child healthcare (MCH), including improving breastfeeding initiation and duration, and outcomes related to maternal and newborn health status, such as improved maternal mental health 17. Several interventions have been implemented to improve continuity, for example, MCH booklets introduced in Angola 18. Previous reviews on MCH in high-income countries have also emphasised the importance of strengthening continuity, highlighting this as a priority area for research in LMICs 19…”
Section: Introductionmentioning
confidence: 99%
“…Hence, efforts to improve the quality of care and sensitise users should be simultaneously undertaken to promote maternal and child health in Angola. To bridge the gap in quality of care, health workers should be trained adequately before and during an intervention is introduced [28,36]. Third, the results suggest that pregnant women in low socioeconomic groups, especially those with lower education, on lower economic levels, and living in rural areas, require intensive support to utilise MNCH services at recommended levels.…”
Section: Implications For Practicementioning
confidence: 99%